Research on performance evaluation of multiple recycling asphalt and multiple recycling asphalt mixtures - Yu, Xin; Wang, Sudi; Wang, Jie; Cai, Qinfeng; Li, Dong; Wang, Linbing (Frontiers in Materials, 2025)
Whether reclaimed asphalt pavement can be reused multiple cycles has become a focal issue in the industry. This paper investigates the macroscopic physical property changes and microscopic four-component alteration mechanisms of multiple recycling asphalt, simulates the multiple recycling processes of asphalt mixtures through laboratory tests, determines the mix proportions of multiple recycling asphalt mixtures through Marshall test, and evaluates the pavement performance of the mixtures using high-temperature wheel tracking test, semi-circular bending test, and freeze-thaw splitting test. The results indicate that after multiple recycling, multiple recycling asphalt exhibits poorer rheological property; high-temperature performance of multiple recycling asphalt mixture is improved, and low-temperature performance of multiple recycling asphalt mixture is significantly degraded. The solubilization of rejuvenator in old asphalt intensifies with increasing rejuvenator dosage but decreases exponentially with the increasing number of recycling cycles. The high-temperature stability of recycled asphalt mixtures gradually increases with the number of recycling cycles, while water stability shows low sensitivity to the number of recycling cycles. After the third recycling, the Marshall volume indicators of the recycled asphalt mixtures can meet the regulatory requirement. After the second recycling, the low-temperature anti-cracking performance of the recycled mixtures deteriorates rapidly. In summary, when asphalt mixtures undergo multiple recycling, special attention should be paid to the restoration of their low-temperature property.